The Potential Effects of Oxidative Stress-Related Plasma Abnormal Protein Aggregate Levels on Brain Volume and Its Neuropsychiatric Consequences in Parkinson's Disease. (16th August 2021) - Chen, Pei-Chin; Yu, Chiun-Chieh; Chen, Yueh-Sheng; Lu, Cheng-Hsien; Chan, Shan-Ho; Chou, Kun-Hsien; Chen, Mei-Hsiu; Chen, Meng-Hsiang; Lin, Wei-Che
Abstract : Background . Oxidative stress has been implicated in the pathogenesis of many diseases, including Parkinson's disease. Large protein aggregates may be produced after the breakdown of the proteostasis network due to overt oxidative stress. Meanwhile, brain volume loss and neuropsychiatric deficits are common comorbidities in Parkinson's disease patients. In this study, we applied a mediation model to determine the potential influences of oxidative stress-related plasma abnormal protein aggregate levels on brain volume and neuropsychiatric consequences in Parkinson's disease. Method . 31 patients with PD and 24 healthy controls participated in this study. The PD patients were further grouped according to the presentation of cognitive decline or not. All participants received complete examinations to determine plasma abnormal protein aggregates levels, brain volume, and neuropsychiatric performance. The results were collected and analyzed in a single-level three-variable mediation model. Results . Patients with PD cognitive decline exhibited higher plasma NfL levels, decreased regional brain volume, and poor neuropsychiatric subtest results compared with PD patients with normal cognition, with several correlations among these clinical presentations. The mediation model showed that the superior temporal gyrus completely mediated the effects of elevated plasma NfL levels due to the poor psychiatric performance of picture completion and digit span. Conclusion . This study provides insight into the effects of oxidative stress-related plasma abnormal protein aggregate levels on regional brain volume and neuropsychiatric consequences in Parkinson's disease patients.